Financial Accountability in a Newly Licensed Zakat Institution: A Qualitative Case Study of Baitulmaal Munzalan Indonesia's Bandung Branch - Nurul Afifah (JOURNAL EKONOMI, KEUANGAN, PERBANKAN DAN AKUNTANSI SYARIAH, 2025)
Zakat institutions occupy a peculiar governance position. They administer donor funds under an explicitly theological mandate of amanah, yet Indonesian law subjects them to the same reporting logic applied to secular nonprofits. This qualitative case study examines how a branch office of Baitulmaal Munzalan Indonesia (BMI) in Bandung enacts financial accountability in the structural absence of an external audit, four years after opening and two years after formal licensing as an Amil Zakat Institution (Lembaga Amil Zakat, LAZ). Field data were collected through unstructured interviews with the branch manager and program and administration staff, direct observation, and documentation, including monthly zakat distribution records for 2023 and consolidated financial reports for 2024. Findings show accountability practiced across four dimensions, honesty, program, performance, and financial, but resting almost entirely on self-report distributed through informal channels such as WhatsApp bulletins rather than independently verified disclosure. The branch's own admission that it has never undergone a sharia or financial audit since licensing exposes a gap between the regulatory ideal codified in Law No. 23/2011 and Government Regulation No. 14/2014 and branch-level operational reality. The study argues that this gap is not merely a compliance lapse but a structural feature of how national zakat networks devolve financial authority to branches faster than they devolve audit infrastructure, and it proposes a tiered interim-review mechanism for newly licensed branches as a corrective